The chemical, heavy metal and microbial quality of well water in an urbanised village in the Klang Valley - Ambu, S.; Yong, S.F.Y.; Lim, Y.A.L.; Wah, M.J.; Chen, D.K.F.; Ooi, S.S.; Lee, S.P.; Tan, T.M.; Goh, M.Y.; Nyanachendram, D. (International Medical University, Malaysia, 2014)
Background: The public health issue of consuming groundwater is a major concern because people often extract groundwater directly from the aquifers either through wells or boreholes without treating it with any form of filtration system or chlorine disinfection. Based on the Malaysian National Drinking Water guidelines the current study was designed to provide a better understanding on the variable factors that are influencing the quality of well-water in an urbanised village in Malaysia. Well water quality assessment of heavy metals, chemicals, microbial and physical parameters were carried out for Sungai Buloh Village in the Klang Valley to ensure it was safe for human consumption.